expand (x+1)³
please give the correct answer I will give you brainiest answer
Answers
Answered by
4
Step-by-step explanation:
Hope it helps you✨...
Thanks☸
Answered by
2
Answer:
Step-by-step explanation:
=>So let x be ‘a’ and 1 be ‘b’
SUBSTITUTING THE VALUES→
=>(x+1)^3=(x)^3+(1)^3+3(x)(1)(x+1)
=x^3+1+3x(x+1)
=x^3+1+3x^2+3x.
☞So x^3+3x^2+3x+1 is the required answer.
HOPE IT HELPS.
Similar questions
Math,
4 months ago
Computer Science,
4 months ago
Science,
4 months ago
Social Sciences,
9 months ago
Math,
9 months ago
Art,
1 year ago